Pengelolaan Destinasi Wisata Danau Toba Menurut Persepsi Masyarakat Setempat - afrilia elizabet sagala (Jurnal Pariwisata Indonesia, 2021)
In tourism development, community participation is very important. Community participation does not just appear but must start from the right perception of tourism. Local people, with all their perceptions about tourism management, have been involved in tourism management. The purpose of this study was to determine the local community's perception of the manager of the main tourism destinations and to determine the sustainable tourism development model in Simanindo District, Samosir Regency. This type of research is a social survey and descriptive-quantitative. The technique used in sampling is the Franc Lynch method, with a sample of 95 people as respondents, aged 15-64 years old. The type of data used is primary by using a questionnaire with a Likert scale in each question. The data analysis technique used is value perception and multiple regression analysis. The results of this study show: 1) The percentage of the average value of the independent variable is 85%, this means that the perception of the local community about the management principles of Lake Toba tourist destinations is in a positive or good area 2) Sustainable tourism development has a positive relationship and influenced simultaneously by service, attractiveness, human resources, environment, and participation. Therefore, the sustainable tourism development model must emphasize the attractiveness and human resources in Simanindo District.